Alleged cases of syphilis immortalized in the Krakow Altarpiece by Veit Stoss in the light of new research on the origins of the disease in Europe - Grzegorczyk, Wiesław; Grzegorczyk, Joanna; Grzegorczyk, Krzysztof (European Journal of Clinical and Experimental Medicine, 2016)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Syphilis is believed to occur in Europe as early as at the end of the fifteenth century when it was carried to Europe from America by Columbus’ sailors in 1493 (“Columbian” theory). In the nineteenth century this theory was questioned; reference was made to historical sources, pointing to the presence of syphilis in the Old World before Columbus (“preColumbian” theory). In 1933 a book was published by a Polish venereologist, professor Franciszek Walter on “dermatological details” of St. Mary’s Altar in Krakow by Veit Stoss. The author drew attention to the characters carved in the altar, which can show symptoms of late congenital syphilis (including saddle nose). Stoss’s work was completed in 1489, that is four years before the first Columbus expedition returned to Europe. If Walter’s hypothesis was true, syphilis would have existed in Europe before the discovery of America. In Krakow even older historical sights, mostly sculptures, can be found which may suggest syphilis in the presented figures. Possible symptoms of syphilis seen in medieval works of art should be differentiated from other diseases, especially leprosy. Modern studies based on modern experimental methods (paleopathological, archaeological, phylogenetic) have not given yet definitive settlement of the dispute between supporters of two main theories of the origin of syphilis in Europe.